Maxillary lateral incisor agenesis; a retrospective cross-sectional study - Naji Ziad Arandi; Shockry Mustafa (Elsevier, 2018)
Objective: This study aims to estimate the prevalence of congenitally missing lateral incisors in a sample of 2662 dental patients in Palestine. Methods: A total of 2662 digital panoramic radiographs were retrospectively examined for the presence of congenitally missing permanent lateral incisors. The radiographs were obtained from the archival records of patients attending a local dental center at the city of Nablus in Palestine. Results: The prevalence of missing lateral incisors among the examined population (n = 2662) was found to be 1.91%. Unilateral agenesis accounted for 66.6% of the total cases that showed at least one missing lateral incisor. Around 79% of the unilateral cases were on the left side while 21% were on the right side. Bilateral agenesis accounted for 33.3% of 34 cases that had at least one congenitally missing permanent maxillary lateral incisor. Conclusion: The prevalence of missing maxillary lateral incisors in this study population was 1.91%) which was within the range reported in different populations. Keywords: Tooth agenesis, Permanent maxillary lateral incisors, Retrospective, Prevalence